'DREAMS D': New Matrix Evaluation for Software Architecture - Rasjid, Zulfany Erlisa; Aldora, Ivana Yoshe; Piyono, Welly; Yulistiani, Risma; Pranoto, Hady (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
The microservices software architecture is highly popular and commonly used in developing large-scale systems. Does this mean that microservices are superior, or could older architectures like monolithic be more adaptable to modern developments? The selection of software architecture is crucial to support overall system performance, quality, and user experience. Effective evaluation also plays a significant role in assessing system performance. In this paper, an evaluation matrix model is proposed, called 'DREAMS D,' comprising of seven vital components to test the quality of systems built using specific architectures. The focus is on microservices and monolithic architecture as our sample Software Architectures. The evaluation is conducted through a systematic review, and each architecture is scored based on factors such as Development, Response time, Error handling, Availability, Maintenance, Scalability, and Deployment. The result shows that microservices architecture scores higher in most evaluation criteria, suggesting better suitability for complex and adaptive systems. However, monolithic architecture may still be appropriate for simpler systems due to its lower cost and straightforward integration. This study provides a structured and measurable framework for assisting developers and organizations in making strategic decisions when choosing or transitioning between software architectures. The DREAMS D matrix can be used as a reference model for future evaluations or as a foundation for extending the framework to other architectural paradigms such as serverless or event-driven systems.